Population decline in California spotted owls near their southern range boundary - Tempel, Douglas J.; Kramer, H. Anu; Jones, Gavin M.; Gutiérrez, R. J.; Sawyer, Sarah C.; Koltunov, Alexander; Slaton, Michèle; Tanner, Richard; Hobart, Brendan K.; Peery, M. Zachariah (The Journal of wildlife management, 2022)
Species worldwide have begun to shift their range boundaries in response to climate change and other anthropogenic causes, with population declines at the trailing edge of a species’ range often foreshadowing future changes in core parts of the range. Therefore, we analyzed a 30-year (1991–2019) data set for the California spotted owl (Strix occidentalis occidentalis) near its southern range boundary in southern California, USA, that included the largest regional population (San Bernardino Mountains) to estimate trends in territory occupancy and reproduction. We then assessed how these demographic rates were affected by habitat, wildfire, fuel treatments, and climate. Mean occupancy declined from 0.82 to 0.39 during our study, whereas reproductive output showed no temporal trends (x̄ = 0.65 young/occupied territory). Territory extinction (extirpation) rates were relatively low in territories with more large trees (≥50 cm dbh), and colonization increased strongly with large tree density for low-elevation territories within the shrub-woodland ecotype but not for higher-elevation territories within mixed-conifer forest. High-severity wildfire had an adverse effect on occupancy: territory extinction rates steadily increased with the amount of high-severity fire within an owl territory during the previous 10 years, while colonization declined to nearly zero when ≥40% of a territory burned at high-severity during the previous 10 years. The effects of high-severity fire were unlikely to be confounded with post-fire fuel treatments, which primarily consisted of the removal, burning, or scattering of brush and small trees and snags (<40.6 cm dbh) and affected much smaller areas than high-severity fire. Of the 40 territories that received fuel treatments within 10 years of a fire, only 3 of them had post-fire fuel treatments that affected >5% of the territory, whereas average area burned at high severity for all 40 territories was 17%. Fuel treatments intended to modify fire behavior and reduce the likelihood of large, high-severity fires led to increases in territory extinction and colonization such that their net effect on occupancy was minimal. Our simulations of occupancy dynamics indicated that high-severity fire accounted for 9.6% of the observed decline in occupancy, whereas fuel treatments effectively accounted for none of the decline. Spotted owl reproductive output was lower at territories where fuel treatments occurred, but low- to moderate-severity fire resulted in much larger, population-level reductions in reproductive output (141 fewer young) from 2006–2019 than treatments (19 fewer young). Thus, the benefits of fuel treatments that reduce fire occurrence and severity appear to outweigh potential short-term costs to spotted owls and their habitat. Because high-severity fire only explained a modest amount of the long-term occupancy decline and much of the decline occurred in the 1990s before large fires occurred, additional factors are likely adversely affecting the owl population and merit further study. Nevertheless, the large observed population decline, limited evidence of owl dispersal among mountain ranges in the southern California metapopulation, and negative effects of increasingly large and severe fire suggest that California spotted owls at their southern range boundary are vulnerable to extirpation. In an era of climate change, owls in the core part of the range will likely become increasingly susceptible to warmer temperatures and increased severe fire activity in the future. Thus, the restoration of historical, low-severity fire regimes through fuels management while maintaining large trees is important to improving owl persistence.